SONGKE SEBAGAI SIMBOL PERDAMAIAN PADA MASYARAKAT MANGGARAI DESA REPI, KECAMATAN LEMBOR SELATAN NTT - Seravin, Yulianus Sevi; Punia, I Nengah Punia; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT Thisxstudy a to find outxhow Songke is a peace symbol in the Manggarai community. Songke is one of the identities and births of the Manggarai community. For the people Songke cloth is not just any cloth but has its own meaning that is implied in every motive and pattern. Most of the time, there is a high position in the cultural life of the Manggarai community. Every tribe or nation of Indonesia has the expertise to support these matters with its own meaning. Starting from the functions of the death ceremony, marriage, and other traditional ceremonies. All meanings are also found in songke cloth, but one that other traditional fabrics do not have. Songke cloth for the Manggarai community is often used as a mediator when conflicts occur in the community. Each songke cloth motif has its own meaning such as the wong kawong, Ranggong. Keywords: kain songke, symbol peace, manggarai comunity.